Ultrasonic characteristics of immune bodies in children with infectious mononucleosis - S. A. Perepelitsa; L. A. Perminova; I. A. Stepanyan; E. V. Zakhar (Журнал инфектологии, 2021)
Diagnostic morphometric criteria for splenomegaly in children with infectious mononucleosis are established using ultrasound. The study included 29 children with infectious mononucleosis. The average age is 11.7 ± 3.5 years. A morphometric measurement of the length, width and thickness of the spleen, elastometry (EM), and lymph nodes were evaluated. The spleen mass was determined by method of O.V. Vozgoment, coefficients: the ratio of spleen mass to body mass (KMS, Km), body length (KI), body surface area (Ks). The average CCM value was 6,47 ± 2,8, the absolute value of the indicator varied from 1,9 to 14,2. According to the CCM, patients are divided into 3 groups: group A – 6 (20,7%), group B – 11 (38%), group C – 12 (41,3%). The average mass of the spleen was 332,5 ± 119.6 g, the CMS – from 7,7 to 14,2, the average value of the indicator – 8,6 ± 1,9. In group B the mass of the spleen, compared with group C is 1,2 times less. In group C the spleen mass is statistically significantly greater compared with groups A and B. In group C, spleen rigidity was increased in 42,9% of cases. The average EM value is 15,8 ± 4,8 kPa. A negative correlation between the average strength between EM and age (r = – 0,65, p = 0,01) was revealed. A direct relationship was found between the mass of the spleen and the CMS, and lymphadenopathy of various localization, often periportal lymph nodes.